Effect of free fatty acids on liposome susceptibility to imidazole antifungals. - Sud, I J (1979)
The presence of free fatty acids in liposome model membranes sensitizes these membranes to the action of the imidazole antifungals, clotrimazole, micronazole, and sulconazole. Unsaturation of the fatty acids is an important variable; the effect of linoleic and oleic acids is much greater than that of stearic acid. The imidazoles differ somewhat in action, with clotrimazole potency greatest both on membranes with and without fatty acids. Sulconazole has very little activity on membranes without fatty acids even at the highest concentrations tested. The data are discussed with reference to the susceptibility of various cells to the imidazoles and the specificity of imidazole action. A modification of the enzymatic method generally used for assay of marker glucose with liposome systems is also presented.